Targeting the phosphatidylinositol 3-kinase/Akt/ mechanistic target of rapamycin (PI3K/Akt/mTOR) signaling pathway in B-lineage acute lymphoblastic leukemia - Simioni, Carolina; Ultimo, Simona; Martelli, Alberto Maria; Zauli, Giorgio; Capitani, Silvano; Neri, Luca Maria (Italian Journal of Anatomy and Embryology, 2018)
Constitutive activation of the phosphatidylinositol 3-kinase/Akt/mammalian target of rapa- mycin (PI3K/Akt/mTOR) network is a common feature of Acute Lymphoblastic Leukemia (ALL), and is frequently observed in the B-ALL subtype, where it plays important roles in the pathophysiology, maintenance and progression of the disease. Aberrant activation of this sign- aling cascade portends a poorer prognosis in both pediatric and adult B-ALL patients. Promis- ing preclinical data on PI3K/Akt/mTOR inhibitors have documented their anticancer activity and some of these novel drugs entered clinical trials as they could lead to a longer event-free survival, reduce therapy-associated toxicity and provide an important preclinical rationale for the use in combination with BCR-ABL Tyrosine Kinase Inhibitors (TKIs) in Philadelphia posi- tive (Ph+) B-ALL, evaluated by cell viability reduction as well as apoptosis and autophagy induction. The importance of new personalized and targeted therapeutic protocols against the PI3K/Akt/mTOR signaling pathway may impact on microRNA (miRNAs) modulation. miR- NAs are involved in the lymphopoietic process, in the control of gene expression of several transcription factors essential for the commitment, differentiation, and apoptosis of hematopoi- etic stem cells and are frequently localized in common breakpoint regions related to tumors or in fragile sites. Preliminary data showed that treatment of B-ALL cells with PI3K/mTOR Small Molecule Inhibitors (SMI) significantly down-regulated the expression of some onco-miRNAs (miR-150, miR-210 and miR-221) described frequently altered in B-ALL. miRNAs could there- fore be considered as promising molecular biomarkers of cancer with prognostic implications and as predictive biomarkers of treatment response, allowing the development of new clinical and personalized protocols.